Pengaruh Good Corporate Governance, Cash Holding, dan Kinerja Keuangan terhadap Pertumbuhan Laba - Maharany, Tyas Adella; Sunarto, Sunarto; Akbar, Islam Ali; Putren, Irenne (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to analyze the effect of good corporate governance, cash holding, and financial performance on profit growth. This research was conducted by analyzing the financial statements of companies in the banking sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The sample used in this study was 15 banking sector companies listed on the Indonesia Stock Exchange during the period from 2019 to 2023 using a purposive sampling technique. The data used in this study is secondary data in the form of financial reports from each company that has been used as a research sample. The variables used in this study are Good Corporate Governance (X1) as the first independent variable, Cash Holding (X2) as the second independent variable, and Financial Performance (X3) as the third independent variable and Profit Growth (Y) as the dependent variable. Panel data regression method is used as a research methodology in this study. Analysis of research results using the help of EViews 12 software. The results showed that the best model is the Common Effect Model (CEM). The results of this study indicate that Good Corporate Governance (Independent Commissioners) partially has no effect on the Profit Growth, Cash Holding partially has no effect on the Profit Growth, Financial Performance (Return On Assets) partially affects the Profit Growth, and simultaneously Good Corporate Governance (Independent Commissioners), Cash Holding, and Financial Performance (Return On Assets) affects the Profit Growth.